2008
DOI: 10.1186/1756-9966-27-62
|View full text |Cite
|
Sign up to set email alerts
|

Chemokine CXCL12 and its receptor CXCR4 expression are associated with perineural invasion of prostate cancer

Abstract: Objective: To identify the roles of CXCL12 and CXCR4 and the associated mechanism involved in perineural invasion of prostate cancer. Methods:The distribution and expression of CXCL12, CXCR4, MMP-2 and MMP-9 in human prostate cancer and in tumor cells invading nerve tissue were studied with immunohistochemical staining. The effects of exogenous CXCL12 and CXCR4 antagonist AMD3100 on PC3 prostate cancer cells invasiveness were assessed in vitro and in vivo. Results:The expression of CXCL12, CXCR4, MMP-2, and MM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(61 citation statements)
references
References 20 publications
3
57
0
1
Order By: Relevance
“…For example, Zhang et al [21] reported SDF-1alpha and CXCR4 to be overexpressed in prostate cancers compared to hyperplastic prostate tissues. Furthermore, overexpression of SDF-1alpha was associated with an increase in perineural invasion of the prostate cancer cells, which can lead to invasion and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Zhang et al [21] reported SDF-1alpha and CXCR4 to be overexpressed in prostate cancers compared to hyperplastic prostate tissues. Furthermore, overexpression of SDF-1alpha was associated with an increase in perineural invasion of the prostate cancer cells, which can lead to invasion and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, a loss of PTEN, p53 and breast cancer type 1 (BRCA1) combined with an upregulation of EGFR, hedgehog, TGF-β/TGF-βR receptor, ECM components/integrins and SDF-1/ CXCR4 and downstream effectors such as PI3K/Akt, small GTPase Rac-1, mitogenactivated protein kinases, NF-κB, MIC-1 and Rho are often detected in metastatic PC cells (11,135,153,(155)(156)(157)(158)(159)(160)(161)(162)(163)(164)(165)(166). It has also been shown that the migration and engraftment of metastatic PC cells in bones, the most common site of PC metastasis, as well as other distant tissues may be mediated in part through the formation of chemoattractant gradients such as SDF-1 released by host endothelial cells and fibroblasts at distant tissues that specifically attract the metastatic PC cells overexpressing CXCR4 (Figure 1) (23,122,(167)(168)(169).…”
Section: Frequent Gene Products and Molecular Pathways Altered In Metmentioning
confidence: 99%
“…The expression levels of CXCL12 and its receptor CXCR4 are higher in human PCa tissues than those of BPH tissues (Zhang et al 2008). It is worth mentioning that the levels of CXCR4 found at the surface of PCa cells are relatively low, but sufficient to elicit biological responses, in particular, the adhesion of PCa cells to endothelial cells or extracellular matrix through a5 and b3 integrins (Engl et al 2006b).…”
Section: Chemokines and Chemokine Receptors: Correlation With Pca Dismentioning
confidence: 99%
“…In vitro, CXCL12 can stimulate the invasion of PCa cells, while the CXCR4 antagonist AMD3100 inhibits invasiveness (Zhang et al 2008). The stimulation of invasion by CXCL12 involves in particular an induction of the matrix metalloprotease MMP-9, through an activation of PI3K and MAPK pathways (Chinni et al 2006).…”
Section: Chemokinesmentioning
confidence: 99%